Politics, History, and Culture: Comments on Anu Lounela’s “Sovereignty and Violence” - Tsing, Anna (Suomen Antropologi, 2009)
Comments delivered during Anu Lounela’s public defense of her Ph.D. Dissertation, ‘Contesting Forests and Power: Dispute, Violence, and Negotiations in Central Java’, September 26, 2009